The Role of Psycholinguistics in Addressing Learning Disabilities (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Psycholinguistics is an intersection of linguistics and psychology that deals with the study of language processing methods, that is, how people understand, produce, acquire, or lose language. Also, psycholinguistics is important in the study of all branches of linguistics, such as phonology, morphology, syntax, semantics, and learning to read and write. In addition, this science covers cognitive processes involved in information processing. Some aspects of psycholinguistics are discussed below.